2023
DOI: 10.1039/d3ob00376k
|View full text |Cite
|
Sign up to set email alerts
|

Tetramate derivatives by chemoselective Dieckmann ring closure ofallo-phenylserines, and their antibacterial activity

Abstract: A general route which provides direct access to substituted bicyclic tetramates, making use of Dieckmann cyclisation of oxazolidines derivatives derived from allo-phenylserines, is reported. Of interest is the high level...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This outcome further confirmed that the C5-ethyl ester was most likely to be on the same face as the C2 and C4-aryl substituents, which is consistent with Dieckmann cyclisations of similar bicyclic tetramate derivatives. 4,5 Moreover, this work also showed that -NCH(Ar)Naminal systems are accessible, and whose better stability relative to -NCH(Ar)Ohemiaminal ether systems was likely assisted by the electronic withdrawing properties of the tetramate ring.…”
Section: Papermentioning
confidence: 64%
See 4 more Smart Citations
“…This outcome further confirmed that the C5-ethyl ester was most likely to be on the same face as the C2 and C4-aryl substituents, which is consistent with Dieckmann cyclisations of similar bicyclic tetramate derivatives. 4,5 Moreover, this work also showed that -NCH(Ar)Naminal systems are accessible, and whose better stability relative to -NCH(Ar)Ohemiaminal ether systems was likely assisted by the electronic withdrawing properties of the tetramate ring.…”
Section: Papermentioning
confidence: 64%
“…8 Such a process is not dissimilar to the biosynthesis of tetramate natural products. 9,10 We have also shown that allo -arylserines 1f close by the conventional route A pathway 5 to give tetramate 4e via the Dieckmann cyclisation of the major malonamide diastereomer 2g , but interestingly, the minor 2,5- trans malonamide 2e diastereomer derived from threo -aryl serines 1e has been found to ring close by route B to give tetramate 5e . The exclusive chemoselective formation of tetramates 4e and 5e can be explained via steric effects, in which the bulky C2- t -Bu and C4-aryl groups prefer to reside on the less hindered exo -face of the bicyclic lactam.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations